Structural Analysis of GitLab\'s Users and Projects Networks - Hadi Safari; Nazanin Sabri; Faraz Shahsavan; Behnam Bahrak (International Journal of Information and Communication Technology Research, 2020)
GitHub has long been perceived as the exclusive provider of hosting for software development in the minds of many programmers. However, it is far from the only available service out there. GitLab is one of the many platforms offering similar capabilities, which has experienced rapid growth in recent years. GitLab currently holds the second-largest collection of repositories among its competitors. Despite its rapid growth, little attention has been paid to this website by academia. This lack of information with regard to users and projects on the platform, as well as the fast increase in the number of GitLab users, motivated us to conduct the current study. In this paper, we perform social network analysis on the data we have collected from the public users and repositories of GitLab. We observe that GitLab is similar to other code-hosting services with regard to its network structure. We also find that the most influential users and projects on the website, are associated with the founding team of GitLab. We further analyze the collaboration and membership networks and, among other things, find that both graphs display high values of assortativity with regard to node degree. The relations between various attributes of projects have also been analyzed.